INTEGRASI LEMBAGA PENYELESAIAN SENGKETA ALTERNATIF DALAM PROSES ACARA PERADILAN PERDATA: STUDI TENTANG PUTUSAN PENGADILAN YANG DI MEDIASI BERDASARKAN PERMA NOMOR 1 TAHUN 2008 - AAN Roy Sumardika (University of Udayana, 2014)
Mediation process means dispute resolution through negotiation process for obtaining a peace agreement between the parties by using a third party in settling the dispute. Article 130 HIR/154 RBg determines peace efforts may use since the trial began before a judge hands down the dispute. Mediation as part of the Alternative Dispute Resolution is a process outside the court, but Indonesian Supreme Court Rules No. 1/2008 integrates it in the court proceedings and allows the mediation process at the level of legal remedy. So the problem investigated is the court decision re-mediated and the peace agreement mediation results. The method used normative legal research by Legislation Approach and to deepen the research study also use a Legal Concept Analysis Approach which is intended to establish a view and legal arguments in solving the problem at hand. Case that has been decided by the courts is not possible to re-mediated. The mediation process at the level of legal remedy is contrary to the law, especially the provisions of Article 130 HIR / 154 RBg. Indonesian Supreme Court Rules as rules are hierarchically under the law (HIR/RBg) not justified material being regulated substance exceeding material are governed by higher laws. So Indonesian Supreme Court Rules No. 1/2008 can not be a legal basis to regulate the integration of mediation into the docket particularly about mediation at the level of legal remedy because the principle of lex superiori derogat legi inferiori and the principle of lex specialis derogat legi generali not met.